Is Microcredit a Form of Risk for Pastoral Households of Inner Mongolia’s Semiarid Rangelands? - J. Zhang; Huntsinger, L.; Li, Y.B; Li, W.J.* (Rangeland Ecology & Management, 2018)
Microcredit loans are now common for Inner Mongolian pastoralists and are encouraged by government policy on the basis of their previous success for poverty alleviation. However, the effects of the highly variable weather characteristics of many semiarid rangelands on the efficacy of microcredit have not been fully examined. Pastoralists in our study area are often trapped in a vicious cycle of borrowing more each year to pay for previous debt and the next year’s production. Instead of helping to maintain herds through bad years, microcredit has often led to reduced herds and assets. To understand why, a qualitative, interview-based approach was used to determine the kinds of loans taken out and why they are taken out, as well as to assess household livestock sales, income, and costs in three villages. In poor years, 82% of households used loans to purchase winter forage. However, borrowers sold more livestock because the standard 1-yr loan term, combined with weather and market conditions, often forced sales for repayment. Weather and market variation made annual income and costs difficult to anticipate. Loans became an added household risk, another way that environment can influence the social and economic interactions of a rangeland social-ecological system. Longer-term loans could smooth the uncertainty of weather and market conditions, and supplementary measures such as government subsidies or forage insurance could buffer the inevitable but unpredictable bad years. Globally, study of the impacts of nonequilibrial ecological dynamics on economic and policy institutions would help to understand why many development initiatives have failed in such systems.